Comparison of the Contents Pancasila Education and Citizenship From 1975-2013 Curriculum in Indonesian at The 21st Century - Gunawan Santoso; Mamun Murod (Jurnal Ekonomi, 2021)
Abstract The study are philosophically Citizenship Education curricular subjects and is a learning tool creates learners who have mental Pancasilaist in word, deed and behavior in everyday life. Civics is the best material is original from Indonesia is not copied from other countries, including the Pancasila, the 1945 Constitution, the Republic of Indonesia, national unity, and the Red and White. The findings of this study also have implications for the development of scientific development theory and Citizenship Education in terms of the future of Indonesian high school curriculum. This research uses the method of literature analysis with grounded theory is a qualitative research method that uses a number of systematic procedures to develop a theory compiled inductive. Research grounded theory, this research inductive research techniques, emphasizes observation and develops a base of "intuitive" relationship practices between variables. The establishment of Citizenship Education in the Curriculum 1975 with the name of Moral Education Pancasila (PMP). The material is civics, national history, events after Indonesia's independence, the 1945 Constitution, each pancasila principle, the message of the importance of development (such as the five-year development plan and GBHN) for the Indonesian nation, specific state doctrines, discussing moral issues and so on, the vision of its mission is oriented towards value inculcation with the content of the values of Pancasila and the 1945 Constitution. In the 1984 PKn curriculum, Pancasila Moral Education (PMP) aims to strengthen morality and improve the ethics of students so that they can face and respond to all kinds of changes in living conditions in the future. Then the 1994 curriculum, where "Pancasila Moral Education" (PMP) has changed its name to "Pancasila education and citizenship" (PPKn). Curriculum in 2004, Initially the subjects were combined into one, because the content of Civic Education is derived from Pancasila itself. It is then broken down into its own subjects because Citizenship Education is considered important to be taught to students. Then PKn Curriculum in 2006, developed a body of knowledge known to have a systemic paradigm in which there are three domain citizenship education, namely academic domain, curricular domain, and socio-cultural domain. Furthermore, curriculum in 2013, Draft from Puskurbuk, Ministry of National Education in 2012, PKn 2006 will be changed to the lessons of Pancasila and Citizenship Education abbreviated PPKn.